Resistance Training's Ability to Prevent Cancer-induced Muscle Atrophy Extends Anabolic Stimulus - Padilha, Camila S. [UNESP]; Cella, Paola S.; Chimin, Patrícia; Voltarelli, Fabrício A.; Marinello, Poliana C.; De Jesus Testa, Mayra Tardelli; Guirro, Philippe B.; Duarte, José A. R.; Cecchini, Rubens; Guarnier, Flávia A.; Deminice, Rafael (Wolters Kluwer, 2021)
Purpose This study aimed to determine the role of mammalian target of rapamycin (mTORC1) activation and catabolic markers in resistance training's (RT) antiatrophy effect during cachexia-induced muscle loss. Methods Myofiber atrophy was induced by injecting Walker 256 tumor cells into rats exposed or not exposed to the RT protocol of ladder climbing. The role of RT-induced anabolic stimulation was investigated in tumor-bearing rats with the mTORC1 inhibitor rapamycin, and cross-sectional areas of skeletal muscle were evaluated to identify atrophy or hypertrophy. Components of the mTORC1 and ubiquitin-proteasome pathways were assessed by real-time polymerase chain reaction or immunoblotting. Results Although RT prevented myofiber atrophy and impaired the strength of tumor-bearing rats, in healthy rats, it promoted activated mTORC1, as demonstrated by p70S6K's increased phosphorylation and myofiber's enlarged cross-sectional area. However, RT promoted no changes in the ratio of p70S6K to phospho-p70S6K protein expression while prevented myofiber atrophy in tumor-bearing rats. Beyond that, treatment with rapamycin did not preclude RT's preventive effect on myofiber atrophy in tumor-bearing rats. Thus, RT's ability to prevent cancer-induced myofiber atrophy seems to be independent of mTORC1's and p70S6K's activation. Indeed, RT's preventive effect on cancer-induced myofiber atrophy was associated with its capacity to attenuate elevated tumor necrosis factor a and interleukin 6 as well as to prevent oxidative damage in muscles and an elevated abundance of atrogin-1. Conclusions By inducing attenuated myofiber atrophy independent of mTORC1's signaling activation, RT prevents muscle atrophy during cancer by reducing inflammation, oxidative damage, and atrogin-1 expression.
Keywords: CANCER CACHEXIA; MTORC1; MUSCLE WASTING; UBIQUITIN-PROTEASOME